Nutritional characterization of ryegrass silages from Southern Chile using the Cornell Net Carbohydrate and Protein System model - Pedro Melendez; Ingrid Castro; Omid Nekouei (Cogent Food & Agriculture)
The objectives were to evaluate the nutritional characteristics of perennial ryegrass silage from pile and plastic bale wrapping system (BWS) from Southern Chile using the Cornell Net Carbohydrate and Protein System. Between 2019 and 2021, 445 pile and 435 BWS silage samples were collected from 158 dairies and analyzed by NIRS. Dry matter (DM) and crude protein were significantly lower in pile than in BWS: 35.2% vs. 42.2% and 13.3% vs. 13.9%, respectively. Lignin and aNDFom were significantly higher in pile than in BWS; 51.43% vs. 49.1%; and 4.52% vs. 3.85%, respectively. Total acids were lower in BWS (4.53%) than in pile silages (6.27%). Assuming a cow consuming 25 kg of DM from each silage, the predicted metabolizable energy and protein to produce milk were significantly higher for BWS (41.8 Mcal and 462.3 g) than pile silages (40.3 Mcal and 296.6 g), respectively. Predicted fecal N, P, and K, and CH4 yield in rumen were higher in BWS than in pile silages. It is suggested that by feeding smaller amounts of BWS silage, similar milk yield can be achieved than feeding a greater amount of pile silage, with a potential lower excretion of N, P, K, and methane to the environment.